Variants of Currarino Syndrome: Embryological Association and Review of Pertinent Literature. (9th November 2014) - Gupta, Rahul; Sharma, Shyam Bihari; Mathur, Praveen; Goyal, Ram Babu
Abstract : Currarino syndrome is a triad of sacral defect, anorectal malformation and a presacral mass. The diagnosis is usually made late in childhood and about 50% of cases are familial with autosomal dominant inheritance. We present two neonates (one with vestibular fistula, and another with cloacal malformation) with the features consistent with Currarino syndrome, but with Altman's type II sacrococcygeal teratoma, that is, presacral mass having an external sacrococcygeal component also. We believe that this triad should be considered a variant of Currarino syndrome. In first case, excision of the mass along with coccyx, followed by primary Posterior Sagittal AnoRectoPlasty was performed in the same setting. The patient succumbed to death due to septicemia as a result of wound sepsis. Learning from the previous experience, we decided to do a diverting sigmoid loop colostomy followed by posterior sagittal excision of the mass along with coccyx, in same sitting in the second case. There was no recurrence. Though HLXB9 has been identified as the major causative gene in Currarino syndrome, exact pathogenesis is still unclear. We herein highlight the significance of this variant of Currarino syndrome and propose a theory on the basis of an embryological association between the malformation complex.